Faktor-Faktor yang Mempengaruhi Peran Istri Nelayan dalam Meningkatkan Pendidikan Formal Anak di Kelurahan Air Tawar Barat - Dila Rahayu; Fitri Eriyanti (Jurnal Teori dan Riset Administrasi Publik, 2023)
The background to this research is that the dual role of a fisherman's wife draws attention to her children's education which is neglected so that many of the fisherman's children's educational levels are low. However, it is known that in general the education level of fishermen's children is relatively low, however, this is different from that in Air Tawar Barat Subdistrict, where in reality, of the many fishing households in Padang City, there are many fishermen's children who continue their education to tertiary institutions. In this research, researchers used a qualitative approach with descriptive methods in Air Tawar Barat Village. The data obtained was collected through an interview process and documentation study. The results of the research show that the factors that can influence the role of fishermen's wives in improving children's formal education in Air Tawar Barat sub-district are divided into two, namely supporting factors consisting of motivation, the perception of fishermen's wives who want their children to succeed, and the distance between school and home. Meanwhile, the inhibiting factors consist of lack of supervision by a fisherman's wife towards her children, the mindset of the fisherman's wife, the personality of the fisherman's children themselves, and environmental factors where the fisherman's children live.